The Cognitive Control of Eating and Body Weight: It’s More Than What You “Think” - Davidson, Terry L.; Jones, Sabrina; Roy, Megan; Stevenson, Richard J. (Frontiers in Psychology, 2019)
Over the past decade a great deal of research has elucidated the role of cognitive processes in the regulation of energy intake and body weight. An emphasis of much of this work has been on describing the relationships between impairment in these processes and the development of overeating and body weight gain. Accumulating evidence from studies of human and nonhuman animals indicates that the ability of diets high in sugar and saturated fats (a.k.a., western diets) to promote obesity and metabolic dysfunction may be linked to their deleterious effects on the cognitive controls of eating behavior. The results of recent studies also show that consumption of western diets by laboratory animals is associated with the emergence of signs of pathophysiology in brain substrates for memory and cognition, most in notably the hippocampus. Of special concern or findings suggesting that these pathophysiological changes may underlie cognitive deficits early in life and may be precursors to the development of serious late-life cognitive dysfunction. This paper reviews these data and describes how consuming a western dietary pattern could contribute to a vicious cycle of obesity, hippocampal dysfunction and cognitive decline.